An empirical analysis of mergers: Efficiency gains and impact on consumer prices - Céline Bonnet; Jan Philip Schain (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
In this article, we extend the literature on merger simulation models by incorporating its potential synergy gains into structural econometric analysis. We present a three-step integrated approach. We estimate a structural demand and supply model, as in Bonnet and Dubois (2010). This model allows us to recover the marginal cost of each differentiated product. Then we estimate potential efficiency gains using the Data Envelopment Analysis approach of Bogetoft and Wang (2005), and some assumptions about exogenous cost shifters. In the last step, we simulate the new price equilibrium post merger taking into account synergy gains, and derive price and welfare effects. We use a homescan dataset of dairy dessert purchases in France, and show that for two of the three mergers considered, synergy gains could offset the upward pressure on prices post. Some mergers could then be considered as not harmful for consumers.
Keywords: 330